3D seismic imaging of the Nesjavellir geothermal field, SW-Iceland - Amoroso, Ortensia; Napolitano, Ferdinando; Hersir, Gylfi Pall; Agustsdottir, Thorbjorg; Convertito, Vincenzo; De Matteis, Raffaella; Gunnarsdóttir, Sveinborg Hlíf; Hjörleifsdóttir, Vala; Capuano, Paolo (Frontiers in Earth Science, 2022)
We present a detailed seismic imaging of the harnessed Nesjavellir geothermal area, SW-Iceland, which is one of several geothermal fields on the flanks of the Hengill volcano. We map the v_P, v_S and v_P/v_S ratio using seismic data recorded in 2016-2020 and compare them with both a resistivity model of the same area and the rock temperature as measured in boreholes. The results show that the shallower crust (depth less than 1 km) is characterized by low v_P and v_S, and high v_P/v_S ratio (around 1.9). Shallow low resistivity values at similar depths in the same area have been interpreted as the smectite clay cap of the system. At depths between 1 and 3 km the observed low v_P/v_S ratio of 1.64 - 1.70 correlates with high resistivity values. In this area, characterized by temperatures larger than 240°C, the seismicity appears to be sparse and located close to the production wells. This seismicity has been interpreted as induced by the production in combination with naturally occurring earthquakes. At depths greater than 4 km, high v_P/v_S ratio of 1.9 correlates well with low resistivity values.